The Influence of Parenting Patterns and Parents’ Socioeconomic Status on the Interest of Coastal Children in Pursuing Higher Education - Hasanah, Uswatun; Neviyani; Kurniawan, Moh. Usman (Universitas KH. Abdul Chalim Mojokerto, 2025)
This study was conducted to determine the influence of parenting styles and parents’ socioeconomic status on children’s interest in pursuing higher education in the southern coastal region of Jember. The research was motivated by the low participation of coastal children in higher education, largely influenced by limited economic conditions and family upbringing patterns. Using a quantitative survey approach, data were collected from 82 respondents across four coastal districts Ambulu, Wuluhan, Puger, and Kencong through questionnaires and analyzed using descriptive and multiple linear regression techniques. The findings indicate that parenting style has a significant influence on children’s educational interest, while socioeconomic status does not show a significant effect. Democratic parenting, which provides support, freedom, and motivation, enhances children’s desire to continue their studies, whereas authoritarian and neglectful styles tend to lower it. The study concludes that although economic limitations remain an obstacle, parental support and awareness play a more decisive role in shaping educational motivation. Therefore, it is recommended that parents, schools, and local governments collaborate to strengthen educational values and create programs that encourage coastal children to pursue higher education.